2018
DOI: 10.1590/0103-6440201801686
|View full text |Cite
|
Sign up to set email alerts
|

One Abutment at One Time Concept for Platform-Switched Morse Implants: Systematic Review and Meta-Analysis

Abstract: The aim of this systematic review and meta-analysis was to compare the peri-implant vertical bone loss of immediate loading of implant crowns using the one abutment at one time (AOT) protocol and implants with abutment removal (AR). This systematic review with meta-analysis was reported according to the PRISMA statement, with guidance from the Cochrane Collaboration Handbook. A total of 103 publications were identified in the PubMed database and reference lists of examined articles. After the screening of titl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The minimization of the number of connection/disconnections of the abutment has been suggested as a factor for decreased peri‐implant crestal bone resorption, 24,25 and can explain the nonsignificant tendency of the immediately impressed implant sites of this study to have a more coronal position of the mucosal margin. Indeed, the mean 0.22 mm more coronal position of the peri‐implant mucosal margin around immediately impressed implants in this study is approximately the same value reported in systematic reviews of comparative studies for implants treated without abutment connection/disconnections 45–47 …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The minimization of the number of connection/disconnections of the abutment has been suggested as a factor for decreased peri‐implant crestal bone resorption, 24,25 and can explain the nonsignificant tendency of the immediately impressed implant sites of this study to have a more coronal position of the mucosal margin. Indeed, the mean 0.22 mm more coronal position of the peri‐implant mucosal margin around immediately impressed implants in this study is approximately the same value reported in systematic reviews of comparative studies for implants treated without abutment connection/disconnections 45–47 …”
Section: Discussionsupporting
confidence: 85%
“…Therefore, dental implants are generally allowed an undisturbed 6‐week healing period before prosthesis fabrication begins, often with an analog or digital impression. In addition, for implants initially placed in a submerged position, an additional 6‐week or longer healing time is generally used to allow complete healing of the soft tissues after implant uncovering 13,42–47 . This implies that, at a minimum, prosthesis fabrication can potentially be delayed 6 or 12 weeks after implant placement, for 1‐ and 2‐stage implants, respectively.…”
mentioning
confidence: 99%
“…Several systematic reviews recently published are unanimous about the need of standardization of comparable parameters between groups in future studies on the effect of repeated disconnection and reconnection of abutments in peri-implant marginal bone resorption [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Among such heterogeneity, the type of implant/implant–abutment connection, the macro design, and the location of the implant in the arch and the surgical placement protocol of the implant seems to have a greater influence on the initial bone remodeling [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of this multicenter cohort study was to investigate the association of the one‐abutment one‐time concept with MBL around bone‐level implants in relation to other factors. The high number of systematic reviews that have been published on the topic may reflect the interest on maximal bone preservation by the scientific community (Atieh et al., 2017; Perrotti et al., 2019; Santos et al., 2018; Wang et al., 2017). Systematic reviews on therapeutic aspects are usually based on RCTs.…”
Section: Discussionmentioning
confidence: 99%